The Muslim Dress Codes Reception Among Minangkabau Youth in West Sumatra: A Socio-legal Analysis - Medani, Alex; Mairul; Diana Putri, Fadilah; Putra, Marzeko Yosa (Tribakti: Jurnal Pemikiran Keislaman, 2025)
This research attempts to describe the young Minangkabau generation's reception of Muslim dress codes in the public sphere and to reflect on an attempt to reconstruct the local identity of West Sumatra. Although the Muslim dress code has become a common sight and has been uniformly implemented in all educational institutions and government agencies, the reception of the younger Minangkabau generation towards these rules is not always directly proportional to the phenomenon. Using a qualitative approach and interviews with young people in Agam district, Lima Puluh Kota, and Tanah Datar, the research found that most of the sources contacted were unaware of the exact scope and legal enforcement of the regulation. But as Moslem, they agreed with the codes, although the critical notes about the implementation. Besides, only a small percentage opposed it. Considering the further discussion about the contents, the codes should also be implemented proportionately, without binding and forcing another religious follower to avoid the intolerant and discriminatory labels attached to the people of West Sumatra. Further, the reception must also be considered to regulate legal products that are close to Minangkabau community traditions to reconstruct the local identity of West Sumatra.